2013
DOI: 10.1614/wt-d-12-00071.1
|View full text |Cite
|
Sign up to set email alerts
|

Crop Response to Carryover of Mesotrione Residues in the Field

Abstract: Two field residue studies were conducted from 2005 to 2007 in Simcoe, Ontario, Canada, to evaluate the effects of mesotrione soil residues on injury, plant dry weight, and yield of sugar beet, cucumber, pea, green bean, and soybean and to verify the potential of reducing a 2-yr field-residue study (conventional residue carryover) to a 1-yr field study (simulated residue-carryover study) by growing these crops in soil treated with reduced rates of mesotrione applied in the same year. There was a significant dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 14 publications
0
23
0
2
Order By: Relevance
“…However, Riddle et al (2013) noted that the dry mass of sugar beet, green bean and pea plants 40 d after planting was reduced at higher mesotrione application rates (>280 g ai ha −1 ) during the previous season, whereas that of soya bean was not affected, despite plants showing symptoms of phytotoxicity, and the mass of cucumber plants was only reduced at a rate of 560 g ai ha −1 , or four times the recommended application rate. Soya bean is extremely sensitive to this herbicide and can develop symptoms at rates as low as 4 g ai ha −1 (Mitchell et al 2001).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, Riddle et al (2013) noted that the dry mass of sugar beet, green bean and pea plants 40 d after planting was reduced at higher mesotrione application rates (>280 g ai ha −1 ) during the previous season, whereas that of soya bean was not affected, despite plants showing symptoms of phytotoxicity, and the mass of cucumber plants was only reduced at a rate of 560 g ai ha −1 , or four times the recommended application rate. Soya bean is extremely sensitive to this herbicide and can develop symptoms at rates as low as 4 g ai ha −1 (Mitchell et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The symptoms of mesotrione toxicity are not always limited to the classical plant bleaching as described in the literature, but can vary appreciably, and some symptoms such as the crinkled leaves may even be confused with acetanilide damage (WSSA 2007). Riddle et al (2013) observed that symptoms in a carryover trial differed between plant species, with green bean and soya bean exhibiting mainly chlorosis followed by necrosis of the tissue, whereas pea, sugar beet and cucumber plants showed both these symptoms as well as the more characteristic bleaching symptoms. The severity of symptoms on all plant species decreased as the mesotrione application rates decreased (Felix et al 2007;Soltani et al 2007;Riddle et al 2013), a finding similar to that in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations